Planned Behavior Independent Graduation in Beneficiary Families of the Family Hope Program - Helly Ocktilia; Edi Suhanda (Khazanah Sosial, 2025)
This study aims to examine the influence of planned behavior consisting of Attitudes towards Independent Graduation, Subjective Norms, and Perceived Behavioral Control on the desire of Beneficiary Families (KPM) of the Family Hope Program (PKH) to carry out Independent Graduation, namely the decision to end participation as beneficiaries. This study is based on the Theory of Planned Behavior and uses a quantitative method with a descriptive approach. The study population was 268 KPM, with a sample size of 92 people obtained through the Sample Size Calculator application from Raosoft.Inc. The results showed that there was no relationship between Attitudes towards Independent Graduation and Subjective Norms (sig. 0.276). There was a significant relationship between Attitudes and Behavioral Control (sig. 0.003), and between Subjective Norms and Behavioral Control (sig. 0.000). Simultaneously, these three variables had a significant effect on the desire of KPM for Independent Graduation, with an R Square value of 0.712. The effective contribution of each variable is Attitude of 49.43%, Subjective Norm of 21.87%, and Behavioral Control of -0.09%. This finding indicates that personal attitude and social pressure are more influential than self-perception of ability in driving the decision of Independent Graduation.